The Human Rights State : Justice Within and Beyond Sovereign Nations - Gregg, Benjamin Greenwood, 1954- (Book collections on Project MUSE., 2016)
The nation state operates on a logic of exclusion: no state can offer citizenship and rights to all people in the world. In The Human Rights State, Benjamin Gregg proposes ways to decouple rights from citizenship, preserving the nation state, in modified form, and allowing human rights to become part of its domestic constitution.